2021
DOI: 10.3389/fpubh.2021.680726
|View full text |Cite
|
Sign up to set email alerts
|

Education as a Predictor Factor for Knowledge of COVID-19 in Portugal

Abstract: Introduction/Objective: Pandemic of COVID-19 is a major public health problem. At the time of development of this study, no specific medication/vaccine for this disease was approved. Therefore, preventive measures were the main key to control this pandemic. Health literacy (HL) is the ability to obtain, understand and use the information to make free and informed decisions about the health of an individual and to promote community empowerment. Thus, the HL of COVID-19 is important for community empowerment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Several studies in both healthcare workers and the general population confirm the fact that lower educational level is associated with decreased acceptance of the first COVID‐19 booster dose (Chrissian et al, 2022 ; Chu et al, 2022 ; Miao et al, 2022 ; Paul & Fancourt, 2022 ). This could be attributed to the fact that educational level is associated with health knowledge regarding COVID‐19 (Gomes da Silva et al, 2021 ). Increased knowledge regarding COVID‐19 predicts first booster willingness in healthcare workers (Alhasan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in both healthcare workers and the general population confirm the fact that lower educational level is associated with decreased acceptance of the first COVID‐19 booster dose (Chrissian et al, 2022 ; Chu et al, 2022 ; Miao et al, 2022 ; Paul & Fancourt, 2022 ). This could be attributed to the fact that educational level is associated with health knowledge regarding COVID‐19 (Gomes da Silva et al, 2021 ). Increased knowledge regarding COVID‐19 predicts first booster willingness in healthcare workers (Alhasan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…48 Another study done in Portugal reported education as a positive predictor of COVID-19 level of knowledge. 49…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in both healthcare workers and the general population confirm the fact that lower educational level is associated with decreased acceptance of the first COVID-19 booster dose (Chrissian et al, 2022; Chu et al, 2022; Miao et al, 2022; Paul & Fancourt, 2022). This could be attributed to the fact that educational level is associated with health knowledge regarding COVID-19 (Gomes da Silva et al, 2021). Increased knowledge regarding COVID-19 predicts first booster willingness in healthcare workers (Alhasan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%